The Multifaceted Effects of Ashwagandha (Withania somnifera) Root Extract on Physical Performance, Cognitive Function, Mental Health, and Safety in Adults - Zakrzewska, Natalia; Bychowski, Mateusz; Kwaśna, Julia; Załęska, Adrianna; Kaźmierczyk, Izabela; Lenart, Kacper; Górski, Mateusz; Homza, Michał; Bednarek, Szymon; Kulicka, Joanna (Quality in Sport, 2024)
Background: Ashwagandha root extract offers broad therapeutic benefits, enhancing physical performance, mental health, and cognitive function, making it a valuable adaptogenic and nootropic solution. Methods: This study reviews clinical trials on Ashwagandha's effects in adults, analyzing physical performance, cognitive function, mood, sleep, and hormonal balance using validated measures and biomarkers. Results: Ashwagandha supplementation enhanced endurance, strength, and hypertrophy, especially with resistance training. It improved memory, attention, anxiety, and depression, boosted sleep quality, balanced hormones in perimenopause, increased testosterone in men, and aided COVID-19 recovery, all without adverse effects. Conclusion: These findings highlight Ashwagandha's broad-spectrum benefits as a safe and effective therapeutic agent for physical performance, cognitive health, and mental well-being. Further large-scale, long-term studies are needed to refine dosing protocols and expand its clinical applications across diverse populations.